Upaya Meningkatkan Hasil Belajar Fikih Materi Perawatan Jenazah melalui Metode Demonstrasi di MTs Negeri 3 Kulon Progo - Siti Muslimah (Jurnal Pendidikan Madrasah, 2019)
This research focuses on improving the results of fiqh learning by demonstration method to increase the value that has not reached the KKM at MTsN 3 Kulon Progo. This research uses class action research methods to describe the process and learning outcomes through demonstration methods implemented in the form of cycles. Data collection is done through interviews, observation sheets, tests and documentation. Data on student learning outcomes is obtained through tests, then compared to the minimum standards that are indicators of successful research, i.e. most students (+ 75%) Obtain a value of reaching the KKM. Research findings show that increased motivation in demonstrative learning in fiqh subjects can be seen in the learning outcomes i.e. the value of reaching the KKM of 10 students (43%) and 16 students (61%) to 19 students (82%). Demonstration methods can improve student learning outcomes.